The Influence of Regional Tax Revenue Pre-Covid-19 and During Covid-19 on the Economic Growth Level of the Karawang Regency Government - Kurniasari, Dewi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to determine the influence of Pre-Covid-19 and During Covid-19 Regional Tax Revenues on the regional economic level of Karawang Regency, as well as to see how effective Pre-Covid-19 and During Covid-19 Regional Tax Revenues are on the economic growth level of the Karawang Regency area. The research method used is a quantitative research method with primary and secondary data sampling and obtained using SPSS statistics with a population from the Karawang Regency Regional Revenue Agency and the Karawang Regency Central Statistics Agency. The results of this research were obtained Based on the results of hypothesis testing carried out using multiple linear regression tests, there is a significance value of 0.012, which means the value is <0.05 in variables X1 and X2. A higher effectiveness value compared to regional tax revenue during Covid-19, with a greater growth rate in the pre-Covid-19 year compared to the year during Covid-19, in the year during Covid-19 the level of effectiveness of tax revenue increased. The lowest compared to the previous year, namely 89% in 2021. Then the level of economic growth also got the lowest growth percentage compared to the previous year, namely 3.95%, namely in 2020.